Attitudinal Lexemes in Diplomatic Discourse: An Appraisal Analysis of President Prabowo Subianto’s 2025 UNGA Speech - Evi Endarti (UIN Salatiga, 2026)
This study examines how attitudinal lexemes shape Indonesia’s diplomatic stance in President Prabowo Subianto’s 2025 address to the United Nations General Assembly. Drawing on Halliday’s Systemic Functional Linguistics (1994) and Martin and White’s (2005) Appraisal Framework, the analysis examines evaluative patterns across Affect, Judgment, and Appreciation. A total of 60 attitudinal lexemes were identified: 18 Affect lexemes expressing empathy, collective resolve, and shared humanity; 17 Judgment lexemes articulating moral evaluation and leadership expectations; and 25 Appreciation lexemes assessing international institutions, achievements, and global challenges. While the predominance of positive evaluation aligns with UNGA genre conventions, the findings suggest that such positivity also serves a strategic purpose, legitimizing diplomatic authority, reinforcing moral credibility, and preempting dissent through the normalization of consensus-oriented values. This evaluative pattern contributes to the construction of a moralized international identity that implicitly constrains alternative or oppositional perspectives within global governance discourse. By foregrounding linguistic choices rather than political ideology, the study demonstrates how evaluative language operates as a subtle mechanism of diplomatic legitimation on the global stage.